RENAL RISCS IN DETERMINATION OF BRONCHIAL ASTHMA PHENOTYPES - Zh.D. Semydotska; I.A. Cherniacova; G.V. Eremenko (Український Журнал Нефрології та Діалізу, 2015)
The aim of this investigation was to study acid - secretory renal function and acid - base balance in patients with bronchial asthma in order to optimize the diagnostics and treatment from the pposition of phenotyping.